2019
DOI: 10.5860/cal.17.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Research Roundup: Resources on Play

Abstract: We have all heard the phrase “play is a child’s work” but how can we convince parents that play should be a meaningful part of their child’s routine?Play, with its inclusion as one of the critical early literacy practices advocated by the Every Child Ready to Read (ECRR) initiative, may be the hardest sell of the five practices to parents, educators, and even administrators. It may be seen as optional or extra, something to be done after the child has spent time “learning” if there is time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Emerging literature and practitioner-focused writings have indicated that public libraries have been focusing on creating library spaces (Hassinger-Das et al, 2020), providing "loose parts" toys (Swadley, 2021), and offering programs (Ruscio, 2019) to better incorporate and facilitate children's unstructured play. For public library storytimes, the use of play has ranged from offering time and space before and after the program for unstructured and less adult-guided play (Diamant-Cohen et al, 2012), to more actively adult-led short, playful elements during the program (Campana, 2021). Understanding more about how educator-led play, and specifically dramatic play, may be effectively sustained and fostered throughout the entirety of the library storytime program holds potential to benefit children's development and move the incorporation of play in storytimes more toward a model of playful learning.…”
Section: Informal Learning Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging literature and practitioner-focused writings have indicated that public libraries have been focusing on creating library spaces (Hassinger-Das et al, 2020), providing "loose parts" toys (Swadley, 2021), and offering programs (Ruscio, 2019) to better incorporate and facilitate children's unstructured play. For public library storytimes, the use of play has ranged from offering time and space before and after the program for unstructured and less adult-guided play (Diamant-Cohen et al, 2012), to more actively adult-led short, playful elements during the program (Campana, 2021). Understanding more about how educator-led play, and specifically dramatic play, may be effectively sustained and fostered throughout the entirety of the library storytime program holds potential to benefit children's development and move the incorporation of play in storytimes more toward a model of playful learning.…”
Section: Informal Learning Environmentsmentioning
confidence: 99%
“…Previous research on public library storytimes has found that these programs can support a variety of early learning and school readiness skills including literacy, mathematics, and others for young children (Campana, 2021). As child enjoyment is frequently a key motivator for family attendance at storytime (Cahill et al, 2020), it is perhaps not surprising that the field has also emphasized the importance of play in public library storytimes, especially as a method for engaging families and supporting children’s development (Diamant-Cohen et al, 2012; Nespeca, 2012). And while play is an important mechanism for supporting children’s development, some child development scholars have moved beyond play to “playful learning,” where educators or other adults intentionally support learning through play, as a more effective way to support learning and development (Hassinger-Das et al, 2017).…”
Section: Introductionmentioning
confidence: 99%